The Population-Level Effect of Screening for Mycoplasma genitalium on Antimicrobial Resistance: A Quasi-Experimental Study. Issue 9 (September 2021) - Kenyon, Chris; De Baetselier, Irith; Vanbaelen, Thibaut; Buyze, Jozefien; Florence, Eric
Abstract : Background: No studies have evaluated the utility and risks of screening for Mycoplasma genitalium in men who have sex with men taking preexposure prophylaxis (PrEP). We made use of a quasi-experimental design to evaluate the effect of screening for M. genitalium in a demonstration PrEP cohort with 3-monthly follow-up. Methods: We compared the proportion of PrEP participants with M. genitalium clearance, the duration of persistence, proportion with incident symptoms, the incidence of fluoroquinolone and macrolide resistance, and the proportion of noncleared infections with resistance-associated mutations between 2 groups: those in whom the first episode of M. genitalium was treated and those in whom it was not treated. Results: M. genitalium was detected in 70 of 179 individuals. The first episode of infection was treated in 46 individuals. Treatment was not significantly associated with the incidence of symptomatic infections or the acquisition of genotypic resistance. Treatment was associated with a higher probability of clearance of infection but at the expense of increasing the proportion of remaining infections that were resistant. In the nontreated group, the infections that did not clear were less likely to be fluoroquinolone resistant (1/6 [16.7%]) than those that did clear (4/4 [100%]; P = 0.048). In contrast, in the treated group, there was no significant difference in the proportion of fluoroquinolone resistance between the infections that persisted and cleared. Conclusions: If screening and treatment increase the ratio of resistant to susceptible M. genitalium in a population, then this could play a role in the spread of antimicrobial resistance. Abstract : In this quasi-experiment, we found that screening and treating men who have sex with men for Mycoplasma genitalium was associated with a higher probability of clearance of infection but at the expense of increasing the proportion of remaining infections that were resistant.